IMPLEMENTASI PERATURAN DAERAH NOMOR 6 TAHUN 2012 TENTANG RETRIBUSI IZIN GANGGUAN DI KOTA DUMAI - Ramadhian, Febby; Yuliani, Febri (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2015)
National development is an activity which takes place continuously and sustainability that aims to improve the welfare of society both materially as well as spiritually. Dumai, currently doing rapid development especially in terms of the economy. This can be seen from the emergence of a variety of businesses/companies that use Intenitas Great Disorder/high, medium and small scattered in Dumai. The establishment of places of business must have permission of disorder (HO). Interference permits aims to provide protection to entrepreneurs and residents of surrounding communities, as the environmental pollution prevention efforts, the preservation of natural resources and the environment as well as Original Income earner area (PAD). The purpose of the research is to find out and analyze the implementation of Regional Regulation No. 6 of 2012 about the disorder in Dumai city and to know the factors that hampered the implementation of such policiesThe concept of the theory used is the implementation of a policy model of Edward III. This research uses descriptive qualitative research methods. In data collection, the author uses interview techniques, observation, and documentation. By using key informants as a source of information and data analysis.The results of this study lead to the conclusion that the implementation of local regulations Dumai No. 6 of 2012 about the disorder, has not done optimally because there are many businesses in the industrial plant in Dumai City unlicensed nuisance and its location also carelessly place that can harm the environment and surrounding communities. This can occur because of a lack of human resources in fostering the spaciousness, as well as communication and coordination between Badan Pelayanan Terpadu dan Penanaman Modal (BPTPM), and Satuan Polisi Pamong Praja (Satpol PP) has not created properly due to the ignorance of the tasks to be carried out, and attitude the implementers are mutually awaiting orders.Keywords: Implementation, Permit Interference in Dumai City